The Development of Listening and Speaking English Skill Through the Use of ICTs - Zambrano Salcedo, Rusbel; Cedeño Macias, Leticia Mercedes (Ciencia Latina Revista Científica Multidisciplinar, 2024)
This research explores how integrating the Easy English Online platform can improve listening and speaking abilities among 10th-grade students at Tarqui High School in Manta between September to November 2023. In today’s digital age, educators use various ICT-based tools to enhance language learning. The Easy English Online platform is recognized for its user-friendly design and interactive features, making it a central focus of this study. By using a blend of quantitative analysis and qualitative inquiry, this study examines how the Easy English Online platform specifically impacts the development of listening and speaking skills in English language learning. The aim is to provide valuable insights for educators and policymakers seeking to optimize the use of ICTs in educational settings. This research also aims to improve student engagement and proficiency in English language learning to meet the evolving demands of modern education.